2021
DOI: 10.1016/j.jbo.2021.100394
|View full text |Cite
|
Sign up to set email alerts
|

Estimating survival and clinical outcome in advanced non-small cell lung cancer with bone-only metastasis using molecular markers

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 38 publications
0
6
1
Order By: Relevance
“…32 With regard to the influence of bone metastasis on survival, most attention has been given to skeletal-related events (SREs), which impair quality of life and are understood to affect survival directly or indirectly. 33 In the present study, we did not observe specific effect of bone metastasis on PFS, which may indicate that EGFR-TKIs are effective and well tolerated in responders. Brain metastasis is one of the important factors affecting the life and quality of life of patients, with an average natural survival time of about 1-2 months.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…32 With regard to the influence of bone metastasis on survival, most attention has been given to skeletal-related events (SREs), which impair quality of life and are understood to affect survival directly or indirectly. 33 In the present study, we did not observe specific effect of bone metastasis on PFS, which may indicate that EGFR-TKIs are effective and well tolerated in responders. Brain metastasis is one of the important factors affecting the life and quality of life of patients, with an average natural survival time of about 1-2 months.…”
Section: Discussioncontrasting
confidence: 54%
“…In line with our data, the authors observed that pleural involvement as composite variable together with malignant pleural effusion both combined were associated with poor outcomes, which could be explained by the fact that pleural cavity is a natural permeable barrier that can limit the penetration of cancer therapies 32 . With regard to the influence of bone metastasis on survival, most attention has been given to skeletal‐related events (SREs), which impair quality of life and are understood to affect survival directly or indirectly 33 . In the present study, we did not observe specific effect of bone metastasis on PFS, which may indicate that EGFR‐TKIs are effective and well tolerated in responders.…”
Section: Discussionmentioning
confidence: 99%
“…Several hematological markers were reported to suggest a poor prognosis for lung cancer after bone metastasis including hypoalbuminemia, increased ALP and tumor-markers, and systemic inflammation, as evidenced by hyperleucemia, neutrophilia or high C-reactive protein (CRP) level ( 6 , 7 , 20 23 ). In the present study, a formula named Risk-H was established using peripheral blood data, and the high risk significantly reduced the survival time.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease of HbA1c, increase of DKK1 and serum calcium were poor prognostic factors for OS independently of common predictors. In the recent study which explored the prognosis factors of NSCLC with BOM, hypoalbuminemia significantly influenced patients’ survival ( 6 ). In our study, bone metabolic index ALP and nutritional index albumin were included in the Risk-H formula.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation